Effect of Cooking Methods on the Antioxidant Capacity of Foods of Animal Origin Submitted to In Vitro Digestion-Fermentation - Beatriz Navajas-Porras; Sergio Pérez-Burillo; Álvaro Valverde-Moya; Daniel Hinojosa-Nogueira; Silvia Pastoriza; José Ángel Rufián-Henares (MDPI AG, 2021)
The human body is exposed to oxidative damage to cells and though it has some endogenous antioxidant systems, we still need to take antioxidants from our diet. The main dietary source of antioxidants is vegetables due to their content of different bioactive molecules. However, there are usually other components of the diet, such as foods of animal origin, that are not often linked to antioxidant capacity. Still, these foods are bound to exert some antioxidant capacity thanks to molecules released during gastrointestinal digestion and gut microbial fermentation. In this work, the antioxidant capacity of 11 foods of animal origin has been studied, submitted to different culinary techniques and to an in vitro digestion and gut microbial fermentation. Results have shown how dairy products potentially provide the highest antioxidant capacity, contributing to 60% of the daily antioxidant capacity intake. On the other hand, most of the antioxidant capacity was released during gut microbial fermentation (90-98% of the total antioxidant capacity). Finally, it was found that the antioxidant capacity of the studied foods was much higher than that reported by other authors. A possible explanation is that digestion-fermentation pretreatment allows for a higher extraction of antioxidant compounds and their transformation by the gut microbiota. Therefore, although foods of animal origin cannot be compared to vegetables in the concentration of antioxidant molecules, the processes of digestion and fermentation can provide some, giving animal origin food some qualities that could have been previously unappreciated.